AN ANALYSIS OF EFL COLLEGE LEVEL LEARNER’S WRITING COMPETENCE IN WRITING AN ARGUMENTATIVE ESSAY - Desi Surlitasari Dewi (CAHAYA PENDIDIKAN, 2018)
One of student’s competence that is expected in college level is to be able to write an argumentative essay. An argumentative essay is a genre of writing that requires students to investigate a topic; collect; generate, evaluate evidence, and establish a position on the topic in a concise manner. The purpose of this study was to find out how EFL learners’ writing competence in writing an argumentative essay. Then, the research question was how are EFL learners’ writing skill in writing an argumentative essay. The research was a descriptive qualitative study, as the data on EFL learners’ writing was analyzed to determine their competence in writing an argumentative essay. The analysis was conducted by describing and explaining the data. The study found that EFL learners’ writing skill in writing an argumentative essay was mostly adequate. In general, the organization was clear and showed the purpose of writing clearly; the content was in logical sequence; the grammar was mostly effective, even though, there were some flaws in the structure of some complex sentences; most of the mechanics were legible and neat, sometimes the word choice is not too appropriate for the context, but it could  convey the message of an essay.